Science Diplomacy and Realism - Malik, Omar Kauser (Journal of Public Policy Practitioners, 2025)
Science diplomacy has attained significance as a non-traditional method of diplomacy. It encapsulates “diplomacy for science”, “science for diplomacy”, and “science in diplomacy” and has emerged as an important way to address global challenges and foster international cooperation. However, this has been done within the ambit of achieving national interest informed by the theoretical underpinnings of realism. In that regard, this qualitative research aimed to use the methodology of a structured literature review through which data has been collected by utilising authentic secondary sources in the form of books, peer-reviewed journal articles, and news sources. It has been understood that neoclassical realists consider economic security an important concern in addition to military power. This ties in with science diplomacy as realist thinking predicates on power and national interests in determining international relations, including the formation of alliances and rivalries in the pursuit of scientific knowledge. Furthermore, states can instrumentalise science diplomacy to advance their influence and national interests in the global arena. This, along with states acting to maximise their power, align with realism. The power maximisation can occur when national interest is secured and strengthened. The national interest can be augmented by utilising science as an effective foreign policy tool. This is because the current century’s global challenges in climate change and food security require scientific innovation and research, which have opened up science diplomacy as a novel avenue for states to ensure their security and national interests.